Percepción sobre el servicio de agua potable en zonas críticas del distrito de San Juan Bautista. Región Loreto. 2020 - Montalvan Bardales, Marden Joffre (2021)
This research work is limited to the evaluation of the social service of drinking water in critical areas of the District of San Juan Bautista, Region Loreto. Inside it; know the continuity of the service, water quality in terms of taste and color, qualification of the operator, frequency of shortages, customer service, among others. The data collection was carried out from February to April 2021, through visits and the application of a survey in the homes of the residents of the study area. Drinking water users supplied by tanker trucks rate the service as regular and usually have a discontinuous service. Respondents report that they have water every day in their homes, which covers their needs on a regular basis (76.2%); Regarding the quality of the water, in terms of taste, they say that it has a strong taste of chlorine (71.4%), and a crystalline color (86.3%). They would like to have drinking water in the taps of the houses (61.38%), the claims about this problem are not presented mostly to the company (58.3%), because the attention is slow (34.5%). In the Chi square test, it only has significance, whether or not to make the payment on the service. They consume around 1000 ml of water/household/week and choose to use filtered or treated water for drinking (67.9%).